1973
DOI: 10.1111/j.1348-0421.1973.tb00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy of Clostridium botulinum and Clostridium sporogenes Strains, and Their Susceptibilities to Induced Lysins and to Mitomycin C

Abstract: An attempt to classify fourteen strains of Clostridium sporogenes and thirty strains of Clostridium botulinum types A, B, C, D, E, and F by numerical taxonomy was made. All proteolytic strains of C. botulinum types A, B, and F and C. sporogenes were classified in the phenon I at a level of 86% S‐value. In the phenon I, these strains coexisted in a mixed‐up fashion, irrespective of conventional species or type of bacteria. A concentrated lysin solution, which was prepared from an induced lysate of a C. botulinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Several investigators have demonstrated that some strains of C. sporogenes cannot be differentiated from proteolytic C. botulinum using phenetic and genetic data (Kiritani et al, 1973;Lee & Riemann, 1970;Wu et al, 1972). In the present study colony-type 11 strains of C. sporogenes were homologous to C. botulinum strain type A I~O in DNA-DNA reassociation assays, and colony-type I strains of C. sporogenes differed from C. botulinum only by 30 to 40 % homology.…”
Section: S N a K A M U R A A N D Othersmentioning
confidence: 61%
See 1 more Smart Citation
“…Several investigators have demonstrated that some strains of C. sporogenes cannot be differentiated from proteolytic C. botulinum using phenetic and genetic data (Kiritani et al, 1973;Lee & Riemann, 1970;Wu et al, 1972). In the present study colony-type 11 strains of C. sporogenes were homologous to C. botulinum strain type A I~O in DNA-DNA reassociation assays, and colony-type I strains of C. sporogenes differed from C. botulinum only by 30 to 40 % homology.…”
Section: S N a K A M U R A A N D Othersmentioning
confidence: 61%
“…A laboratory strain of C. botulinum type A I~O was used as a reference strain for the DNA reassociation assays; this is the representative strain of C. botulinum type A most frequently used in Japan (Iida, 1964;Kiritani et al, 1973;Takumi & Kawata, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Kiritani et al (1973) also stated that a non-toxigenic substrain, NIH-5, obtained from C. botulinum type B, strain NIH, was not susceptible to MC, whereas the toxigenic substrain NIH-19 obtained from the same parent strain was susceptible to the drug. These findings imply that lysogeny is closely related with toxigenicity of clostridia.…”
Section: Discussionmentioning
confidence: 99%
“…Mitsui, Kiritani and Nishida (1973) demonstrated the presence of a lytic agent as well as of phage-like particles in MC lysate of a C. botulinum strain, used the C. botulinum-C. sporogenes group-specifx lysin for taxonomic purposes. The lytic agent of C. sordellii described in the present paper also seems to have taxonomic usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Many phages with empty heads were observed in the lysate if fixation with formalin was omitted and washing was performed in water, suggesting that the phage is fragile or sensitive to osmotic shock. DISCUSSION Kiritani et al (13) reported that bacterial lysis was induced in all toxigenic strains of C. botulinum by treatment with MC and an induced lytic agent(s) was produced in the lysate. Although the presence of bacteriophages or phage-related particles was shown in MC-or UV-induced lysates of C. botulinum types A, B, E, and F (3,4,9), there was no available information concerning relationships between toxicity and lysogeny except for type B (13).…”
Section: Presence Of Bacteriophages In Mitomycin C-induced Culturesmentioning
confidence: 99%